Core endophyte communities of different citrus varieties from citrus growing regions in China - Munir, Shahzad (Sci Rep, 2020)
The native microbiomes of citrus trees play important roles in plant health, with good communication between the native microbiome and the host plant. Here, we report on the native endophytes in 24 citrus varieties in nine citrus growing regions in China; some of the trees were healthy and others had asymptomatic or symptomatic huanglongbing, which is caused by the pathogen Candidatus Liberibacter asiaticus (CLas). We used culture-dependent analysis and characterized the isolates by partial 16S rRNA gene sequencing. The endophytes were compared between different citrus varieties, regions, and disease states (healthy, asymptomatic, and symptomatic). The total number of endophytes isolated from most of the citrus varieties was 10(4)–10(6) CFU/g of leaves, but it differed significantly by disease state, with the highest numbers in the healthy leaves and the lowest in the symptomatic leaves (p < 0.05). Among the citrus varieties, the Valencia variety had the maximum number of endophyte species (22). The most dominant endophytes were Bacillus subtilis, B. velezensis, Curtobacterium luteum, and Microbacterium testaceum. The higher frequency of B. subtilis in the healthy/asymptomatic plants compared to the symptomatic plants suggests that it has a role in huanglongbing resistance. Native endophyte communities in various citrus varieties could be used to improve citrus growth and combat CLas.